Experimental study on energy absorption of foam filled kraft paper honeycomb subjected to quasi-static uniform compression loading - Aminanda, Yulfian; Abd Kadir, Nurdina; Shaik Dawood, Mohd. Sultan Ibrahim; Mokhtar, Hanan (IOP Publishing, 2016)
A statistical analysis was performed first to evaluate the effect of factor and to obtain the optimum configuration of Kraft paper honeycomb. The factors considered in this study include density of paper, thickness of paper and cell size of honeycomb. Based on the three level factorial design,two-factor interaction model (2FI) was developed to correlate the factors with specific energy absorption and specific compression strength. From the analysis of variance (ANOVA), the most influential factor on responses and the optimum configuration was identified. Then, Kraft paper honeycomb with optimize configuration is used to fabricate foam-filled paper honeycomb with five different densities of polyurethane foam as filler (31.8, 32.7, 44.5, 45.7, 52 kg/m3). The foam-filled paper honeycomb are subjected to quasi-static compression loading. Failure mechanism of the foam filled honeycomb were identified, analyzed and compared with the unfilled paper honeycomb. The peak force and energy absorption capability of foam filled paper honeycomb are increases up to 32% and 30% compared to the summation of individual components.